Users' acceptance of online literature databases in a Thai university: A test of UTAUT2 - Chaiyasoonthorn, Wornchanok; Suksa-Ngiam, Watanyoo (My University, 2018)
Online literature databases are important for higher education and research organizations since they represent a vast collection of academic literature that researchers can utilize and review previous research conducted so far. The study aims to test a theory explaining what drive research students adopt online academic literature databases. Unified Theory of Acceptance and Use of Technology 2 (Venkatesh, Thong, & Xu, 2012) is a new theory in Information Systems that should be tested in a different circumstance. The study surveyed 614 respondents in a Thai university. The data are analysed using structural equation modelling (SEM). The results show that behavioral intention and facilitating conditions did not influence use behavior where as other paths suggested by UTAUT2 are still significant. However, only gender moderates the path from facilitating conditions to behavioral intention. The order moderators did not moderate the path suggested by the theory.
Keywords: Online Literature Databases; Thailand; Unified Theory of Acceptance and Use of Technology 2; User Acceptance; UTAUT2